Emotional burnout of healthcare professionals: models, risk factors and protective factors - Assonov, Dmytro (Psychosomatic Medicine and General Practice, 2021)
Emotional burnout (also known as professional burnout, burnout syndrome) is a serious mental health problem for physicians, nurses and other healthcare professionals around the world. The positive dynamics observed between 2014 and 2017 are a cause for optimism and indicate that progress is possible and that more needs to be done to combat burnout. However, despite this progress, the incidence of burnout among physicians is still higher than in the general population. Thus, further research on emotional burnout and systematization of both risk and protective factors is needed. The purpose of this review article is systematization of burnout-related information to outline further ways of development. We analyzed the literature on the topic published over the past 5 years. Databases such as PubMed, APA PsychNet, Google Scholar, Scopus and Web of Science were used to search the literature. Emotional burnout of health workers is associated with a number of risk factors, which can be divided into work-related, social and psychological. The greatest importance in the occurrence of the syndrome hold work-related factors. In addition, a number of professional, social and psychological factors are associated with a decrease in the level of emotional burnout, and therefore have protective properties. The main group of protective factors against emotional burnout are psychological factors, such as emotional intelligence, empathy, optimism, internal control, certain character traits. Despite much research on this topic and the latest advances in psychotherapy, so far, we can only talk about reducing the prevalence of emotional burnout to the level of a decade ago. This suggests that the increase in the prevalence of emotional burnout worldwide has been slowed, but further research on prevention and new, more effective and evidence-based psychosocial methods of dealing with emotional burnout are needed to further reduce the prevalence.